Pelatihan dan Edukasi Investasi Menggunakan Pendekatan 5W+1H Bagi Siswa SMA Negeri 8 Medan - Suriani Ginting; Sonya Enda Natsha S Pandia (Cattleya Darmaya Fortuna, 2024)
This service is carried out for class X students! SMA Negeri 8 Medan which is located on Jalan Sampali, Medan Area District, Medan City, North Sumatra. This community service activity will be held on Friday and Saturday, May 6 and 7 2022. The theme of this community service is investment training and education using the 5W+1H approach for students at SMA Negeri 8 Medan. The aim of this investment education is to equip students with knowledge about investment and financial management. The service method is carried out in two ways, namely the lecture method and training. The results of this service activity have provided knowledge to help students plan their finances for the future and students avoid fraudulent investment fraud.